The Role of Autophagy in the Function of CD4+ T Cells and the Development of Chronic Inflammatory Diseases - Jiung Jeong; Jiung Jeong; Young Joon Choi; Heung Kyu Lee (Frontiers Media S.A., 2022)
Uncontrolled acute inflammation progresses to persistent inflammation that leads to various chronic inflammatory diseases, including asthma, Crohn's disease, rheumatoid arthritis, multiple sclerosis, and systemic lupus erythematosus. CD4+ T cells are key immune cells that determine the development of these chronic inflammatory diseases. CD4+ T cells orchestrate adaptive immune responses by producing cytokines and effector molecules. These functional roles of T cells vary depending on the surrounding inflammatory or anatomical environment. Autophagy is an important process that can regulate the function of CD4+ T cells. By lysosomal degradation of cytoplasmic materials, autophagy mediates CD4+ T cell-mediated immune responses, including cytokine production, proliferation, and differentiation. Furthermore, through canonical processes involving autophagy machinery, autophagy also contributes to the development of chronic inflammatory diseases. Therefore, a targeted intervention of autophagy processes could be used to treat chronic inflammatory diseases. This review focuses on the role of autophagy via CD4+ T cells in the pathogenesis and treatment of such diseases. In particular, we explore the underlying mechanisms of autophagy in the regulation of CD4+ T cell metabolism, survival, development, proliferation, differentiation, and aging. Furthermore, we suggest that autophagy-mediated modulation of CD4+ T cells is a promising therapeutic target for treating chronic inflammatory diseases.